Characteristics of Nitrate Reductase-inactivating Proteins Obtained from Corn Roots and Rice Cell Cultures - Yamaya, Tomoyuki (1980)
Nitrate reductase (NR)-inactivating proteins from corn roots (Wf-9 × 38-11) and rice cell suspension cultures were tested against a partially purified NR obtained from corn leaves (W64A × W182E). The corn protein was purified 921-fold and the rice protein, 1,660-fold using standard purification procedures. Approximate molecular weight values were 75,000 for the corn protein, and 150,000 for the rice protein as determined by Sephadex G-100 gel filtration. The Sephadex-treated proteins were characterized by electrophoresis on polyacrylamide gels. With a running pH of 9.4 the corn protein remained at the origin whereas the rice protein migrated with an R(F) value of 0.49. With a running pH of 4.0 the corn protein migrated with an R(F) value of 0.25. With the corn protein the activities of NR inactivation and hydrolysis of azocasein were detected in the same protein band. The rice protein, however, had no associated protease activity. From sodium dodecyl sulfate gel electrophoresis, there was one major protein band with an estimated molecular weight of 66,000 in corn protein. In rice protein four bands were observed with estimated molecular weights of 73,000, 66,000, 62,500, and 58,500, respectively. Both inactivators had an inhibitory effect on NADH-NR and NO(3)(−) induced NADH-cytochrome c reductase activities but they had less influence on the activities of FMNH(2)-NR and reduced methylviologen-NR. Inactivation of rice cell NR by rice inactivator was reversed by addition of NADH. Inactivation of corn leaf NR by rice inactivator was inhibited by the simultaneous addition of NADH, but rice inactivator-inactivated corn leaf NR could not be reactivated by NADH.